Reflective Thinking Pratices among Secondary School Mathematics Teachers - Tee, Yueh Jiuan (2007)
The study aimed to identify the practice of reflective thinking among secondary school mathematics teachers in teaching and learning process. Reflective thinking in the study encompasses four constructs which are retrospective and predictive thought, critical inquiry, problem-solving skills and, acceptance and use of feedback. The study also tries to identify the factors affecting the practice of reflective thinking. The factors in this study are time constraints, teachers’ perception of mathematics learning, internal and external learning orientation, and effectiveness of problem solving. This is a descriptive correlational study. The instrument of the study is a set of questionnaires based on Likert scales. The questionnaires were adopted from the instruments of several foreign studies (Stout, 1989; Pelsma, Richard, Harriston & Burry, 1989; Korthagen, 1993; Heppner & Petersen, 1982). The respondents consisted of 147 mathematics teachers from 19 secondary schools in Seremban District in Negeri Sembilan. They were selected using multistage sampling which involved simple random sampling and cluster sampling. The questionnaires were distributed to the respondents through the representative of mathematics teacher in each school and were returned to the research via mail. Data collected from the respondent was based on their perception toward reflective thinking practices in teaching and learning. The data were analysed using inferential statistic such as t-test, ANOVA, Pearson correlation and linear regression analysis. Overall, the results of the study revealed that mathematics teachers practise reflective thinking moderately (mean = 3.64). However a strong emphasis was found on retrospective and predictive thought (mean = 3.85) among teachers, while moderate practice was shown in construct critical inquiry (mean = 3.43), problem-solving skills (mean = 3.58) and acceptance and use of feedback (mean = 3.66). Findings showed no significant differences of reflective thinking practices based on teachers’ background factors. Pearson correlation analysis showed significant positive relationships among reflective thinking practices with internal learning orientation (r = 0.46, p < 0.01), effectiveness of problem solving (r = 0.43, p < 0.01), time constrains (r = 0.34, p < 0.01), external learning orientation (r = 0.32, p < 0.01) and teachers’ perception of mathematics learning (r = 0.28, p < 0.01). Multiple regression analysis revealed four factors which significantly affect reflective thinking practices, namely are time constrains, teachers’ perception of mathematics learning, external learning orientation and effectiveness of problem solving. The R2 = .380 implies that the four factor variables explain about 38.0% of the variance in reflective thinking practices. Generally, the findings indicated that the four factors were the most significant factors in explaining the variance of reflective thinking practices.